Oxidation of multiple MiT/TFE transcription factors links oxidative stress to transcriptional control of autophagy and lysosome biogenesis. Issue 9 (1st September 2020) - Wang, Hongfeng; Wang, Nana; Xu, Delai; Ma, Qilian; Chen, Yang; Xu, Shiqiang; Xia, Qin; Zhang, Yan; Prehn, Jochen H. M.; Wang, Guanghui; Ying, Zheng
ABSTRACT: Significant evidences indicate that reactive oxygen species (ROS) can induce macroautophagy/autophagy under both physiological and pathological conditions. Although the relationship between ROS and autophagy regulation has been well studied, the basic mechanism by which ROS affects autophagy and the biological role of this regulation are still not fully understood. In the present study we show that multiple MiT-TFE transcription factors including TFEB, TFE3 and MITF, which are master regulators of autophagy and lysosomal biogenesis, can be activated upon direct cysteine oxidation by ROS. Oxidation promotes the nuclear translocation of these MiT-TFE transcription factors by inhibiting the association of them with RRAG GTPases, which in turn leads to enhanced global gene expression level in autophagy-lysosome system. Our study highlights the role of oxidation of MiT-TFE transcription factors in ROS-linked autophagy, and provides novel mechanism that MiT-TFE transcription factors-mediated transcriptional control of autophagy may govern cell homeostasis in response to oxidative stress, a biological process tightly linked to human diseases including neurodegenerative diseases and cancer. Abbreviations: Bafi A1: bafilomycin A1 ; EBSS: Earle's balanced salt solution; EGFP: enhanced green fluorescent protein; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MTORC1: mechanistic target of rapamycin kinase complex 1; ROS: reactive oxygen species; RPS6KB/p70S6K: ribosomal protein S6 kinase B; TFEB: transcription factor EB; WT: wild type.